Evidence-Based Practices for early childhood teachers for deaf and hard of hearing According to the Council for Exceptional Children Standards (CEC) - Alghamdi, Nouf Ali; Alghamdi, Mazen Abdulrahman (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to identify the most prominent evidence-based practices of teachers of deaf and hard of hearing children in the kindergarten inclusion programs in light of the recommendations of the Early Childhood Department (DEC) of the Council of Exceptional Children (CEC), and to achieve the objectives of this study, a questionnaire was designed consisting of (47 ) A paragraph divided into (7) dimensions of the practices of the Department of Early Childhood (DEC), namely: (assessment, environment, family, education, interaction, teamwork and cooperation, and transition), which were answered by teachers of deaf and hard of hearing children in kindergarten inclusion programs And their number reached (54) teachers. The results showed that the teachers of deaf and hard of hearing children in the kindergarten inclusion programs practice the recommendations of the Early Childhood Department of the Council of Exceptional Children (DEC) to a high degree in general; The highest dimensions were ranked in descending order as follows: (interaction, family, education, environment, evaluation, teamwork and cooperation, transition). The results also indicated that there were no statistically significant differences in the responses of the study sample due to the following variables: educational qualification, specialization, years of experience, training courses. The study recommended the need to issue binding legislation to activate the work of the multidisciplinary team, prepare and activate transitional plans for deaf and hard-of-hearing children, prepare developed models for child integration programs that include all evidence- Based on international standards in educational, rehabilitation and support services.
Keywords: Standards; Deaf and hard of hearing children; Kindergarten; Inclusion programs